Cuidado de si e consciência corporal : aportes foucaultianos para uma educação físia escolar não mecanicista - Bolsoni, Betania Vicensi (2012)
This study starts on the body s contextualization, according to its insertion on the process of brazilian physical education so, then, discuss two different approaches that represent the Academical Physical Education, with corporal mechanicism traits, namely, the developmental and the psychomotricity. Following this step, comes the search on Foucault s late work, to find, in this author, particularly through the self care topic, parameters to examine in which way this resource, combined to the body awareness, allows to go further than the limits of those approaches. Thereunto, we will attach the concept of self care, through its dimensions and characteristics, to the body and, still, we will explore the relation between this concept and the aesthetics of existence topic. We aim to show that the foucauldian self care may be aproximate to the academical physical education ambit, through the concept of body awareness. We will seek to indicate, also, how through this way, it is possible to indicate perspectives beyond the corporal mechanicism traits in Academical Physical Education, presented by those approaches. And in this ambit, go further than those traits, as a way to seek a formative process meaningful to individuals. The assumption embraced on this paper is the foucauldian conception of sel care that allows to, even go beyond the limits of the corporal mechanicism traits approaches in Academical Physical Education, or to attach the body awareness topic, to conceive the Physical Education on a non-mechanical perspective.